2009
DOI: 10.1103/physrevlett.102.207002
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Superconducting Gap of Ultrathin Pb Islands Grown on Si(111)

Abstract: The energy gap Delta of superconducting Pb islands grown on Si(111) was probed in situ between 5 and 60 monolayers by low-temperature scanning tunneling spectroscopy. Delta was found to decrease from its bulk value as a function of inverse island thickness. Corresponding T_{c} values, estimated using bulk gap-to-T_{c} ratio, are in quantitative agreement with ex situ magnetic susceptibility measurements, however, in strong contrast to previous scanning probe results. Layer-dependent ab initio density functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
155
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(166 citation statements)
references
References 33 publications
11
155
0
Order By: Relevance
“…So, for the experiments reported in Ref. 9, g is not sensitive to the change of Si(111) surface crystal ordering from (7 × 7) to ( Note that the first and second data-sets in the present study were considered in our previous work. 2 However, in that paper we performed time consuming calculations invoking the full BdG formalism.…”
Section: B Impact Of the Thickness-dependent Coupling Between Electronsmentioning
confidence: 98%
See 1 more Smart Citation
“…So, for the experiments reported in Ref. 9, g is not sensitive to the change of Si(111) surface crystal ordering from (7 × 7) to ( Note that the first and second data-sets in the present study were considered in our previous work. 2 However, in that paper we performed time consuming calculations invoking the full BdG formalism.…”
Section: B Impact Of the Thickness-dependent Coupling Between Electronsmentioning
confidence: 98%
“…The critical temperature of atomically flat Pb nanofilms with thickness down to a few monolayers on a Si(111) substrate have been measured under different conditions. [3][4][5][6][8][9][10] It was found that superconductivity is not destroyed by fluctuations even when the thickness of the nanofilm is only a single monolayer, 10 and the dependence of the critical temperature on thickness shows oscillations with a period close to two monolayers (ML), 3,5 i.e., the even-odd staggering in the superconducting properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rich variety of unexpected phenomena which were observed has incited research also in temperature ranges far above the superconduction transition temperature T C of Pb. Examples of these observations are the strong dependence of the Schottky barrier on the exact atomic structure 6 , the formation of magic height islands 7 , anomalies in the superconductivity transition temperature [8][9][10] , oscillations of the work function and extremely long excited state life times 11,12 , and the observation of a Rashba-type spin splitting 13 . The origin of many of these phenomena lies in the peculiar electronic structure of Pb on Si(111) manifested in the high in-plane effective mass [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Since for semiconductor heterostructures with ultralow electron concentrations Fermi wavelengths can be of the order of 100 nm, size quantization or Coulomb blockade ͑CB͒ effects are comparably easy to observe in these systems at low temperature. Consequently, the detailed structure of interfaces and defects on the atomic scale are only of minor relevance and, thus, ͑Ohmic͒ contacts for transport studies are well defined on this length scale.…”
Section: Introductionmentioning
confidence: 99%